Pengaruh Digital Payment (Brimo) Terhadap Kepuasan Keuangan Pada Umkm Di Kabupaten Bangkalan - Sofiyatun Naimah; Arie Setyo Dwi Purnomo; Prasetyo Nugroho (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2023)
Financial transactions using technology are developing in Indonesia, one of which is digital payments. Bangkalan Regency is experiencing significant changes in MSME payment and financial patterns in line with the adoption of digital payment technology. Therefore, it is important to understand the specific impact on MSMEs in the area. This research aims to determine the effect of digital payments on financial satisfaction among MSMEs in Bangkalan district, especially in terms of financial satisfaction. This research uses quantitative methods by collecting data using questionnaires and interview techniques. The research subjects were MSMEs in Bangkalan Regency and samples were taken using random sampling technique. The research results confirm that the adoption of digital payments has a significant positive impact on the level of financial satisfaction of Micro, Small and Medium Enterprises (MSMEs) in Bangkalan Regency. This finding is supported by the results of a simple linear regression test analysis, where the significance value (Sig) is 0.000, much smaller than the significance level Î± = 0.005 (5%). The research hypothesis (H1) which states that